1984
DOI: 10.1007/bf02343428
|View full text |Cite
|
Sign up to set email alerts
|

Screening for vesicoureteral reflux in children using real-time sonography

Abstract: One hundred and ten children, ages 6 days to 14 years, were investigated for vesicoureteral reflux (VUR) using ultrasound before voiding cystourethrography (VCU). Sonographically a VUR was assumed if a retrovesical dilated ureter and/or an increase of the separation of the central renal echo complex (CRC) could be detected. By means of sonography VUR grades III and IV were seen in 100%, grade II in 84% of all cases. There was a false positive rate of 10%. Sonographic reflux study is a sensitive and specific sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 7 publications
2
25
0
3
Order By: Relevance
“…describe the reference standard in sufficient detail to permit replication; 115,123,149,165,187,191,195,199,202 six studies reported insufficient detail to allow assessment of the avoidance of test review bias, 115,123,187,195,199,202 and three studies reported insufficient detail to allow assessment of the avoidance of disease progression bias. 165,187,195 The remaining study used direct radionuclide voiding cystography as the reference standard.…”
Section: Figure 25 Standard Ultrasound For the Detection Of Reflux: Smentioning
confidence: 99%
See 2 more Smart Citations
“…describe the reference standard in sufficient detail to permit replication; 115,123,149,165,187,191,195,199,202 six studies reported insufficient detail to allow assessment of the avoidance of test review bias, 115,123,187,195,199,202 and three studies reported insufficient detail to allow assessment of the avoidance of disease progression bias. 165,187,195 The remaining study used direct radionuclide voiding cystography as the reference standard.…”
Section: Figure 25 Standard Ultrasound For the Detection Of Reflux: Smentioning
confidence: 99%
“…Where studies reported more than one data set for the same population, only one data set was included in further analyses; this was to prevent duplicate inclusion of the same study participants. One study 123 reported data using cut-off thresholds of both reflux grade 2 or above, and reflux grade 3 or above; a second study 199 reported data using cut-off points of both reflux grade 2 or above, and presence of any reflux; data for the lower cut-off were used in both cases. One study 124 reported data by patient and by renal unit.…”
Section: Figure 25 Standard Ultrasound For the Detection Of Reflux: Smentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have used sonography to detect VUR, but the effectiveness of ultrasound in the diagnosis of reflux has so far been limited [5,6]. Schneider et al [6] reported in 1984 that, by means of real-time sonography, VUR grades III and IV were detected in 100% and grade II in 84% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to replace VCU with less invasive tests. Ultrasono graphy involves no ionizing radiation and has been pro posed for the detection of VUR [3,[5][6][7], In a recent study, ultrasound cystography has been proposed as an alterna tive to standard VCU for the detection of reflux [2], Color flow Doppler sonographic (CFDS) measurement of the …”
mentioning
confidence: 99%